Eksistensi Tarian Kuda Lumping pada Masyarakat Sunda Berdasarkan Dimensi Tri Tangtu: Sebuah Kajian Hermeneutik - Penti Aprianti; Bartolomeus Samho; Rudi Setiawan; Oscar Yasunari (Sapientia Humana: Jurnal Sosial Humaniora, 2023)
Kuda Lumping or ébég is a typical Sundanese traditional dance that requires the presence of spontaneity when it is played. In it, the elements of profane from the dance and the elements of sacred from its rituals are combined as a medium for the manifestation of the spiritual to the material. It is said that spiritual power is present in the human world through this spontaneity. This is why trance often occurs in the riders of Kuda Lumping as a medium for the presence of spiritual power. The Sundanese people with the Tri Tangtu philosophy believe that mediation through Kuda Lumping is a way for the community to communicate with Sang Hyang or Batara Tunggal. In this paper, the exploration of cultural hermeneutic studies on the Kuda Lumping dance will be discussed based on the dimensions of Tri Tangtu.